Totalitarian Communication : Hierarchies, Codes and Messages - Postoutenko, Kirill; Postoutenko, Kirill (Bielefeld, Germany transcript Verlag)
By using history and theory of communication as an integrative methodological device, this book reaches out to those properties of totalitarian society which appear to be beyond the grasp of specific disciplines. Furthermore, this functional approach allows to extend the analysis of communicative practices commonly associated with fascist Italy, Nazi Germany and Soviet Union, to other locations (France, United States of America and Great Britain in the 1930s) or historical contexts (post-Soviet developments in Russia or Kyrgyzstan). This, in turn, leads to the revaluation of the very term (S1(Btotalitarian(S0(B: no longer an ideological label or a stock attribute of historical narration, it gets a life of its own, defining a specific constellation of hierarchies, codes and networks within a given society.s
English
Keywords: Media studies; Sociology; Totalitarianism; Communication; Discourse; Media; Europe 1900-1945; Society; Sociology of Media; History of the 20th Century; Media Aesthetics; European History; Sociology